Activities of the Department of Economics and agricultural production UAАS (1956–1962) under the leadership of academics I. Romanenko and L. Kletskyy - Vavrisevich, O. M. (History of science and technology, 2015)
Based on historical and scientific analysis revealed the main directions of research work of the Department of Economics and Agricultural Production of the Ukrainian Academy of Agricultural Sciences. Research teams of economists working on a number of theoretical, methodological and practical issues, and achieved significant results.